IMPLEMENTATION OF AUGMENTED REALITY IN KUNINGAN DISTRICT TOURISM BROCHURE USING SURF ALGORITHM (SPEEDED-UP ROBUST FEATURES) - Nadya Syifa Nurhadiyah; Tito Sugiarto; Nunu Nuhraga; Elin Herlina (Balong International Journal of Design, 2019)
AbstractThe Youth Sports and Tourism Department (DISPORAPAR) is an institution that provides information in a variety of fields, including Youth, Sport, Tourism Destination, Institutional and Partnership, and Marketing. In the field of marketing, the promotion of tourist attraction that has been carried out by DISPORAPAR Kuningan Regency is by using brochure media and Instagram social media, where using the media is less than optimal visualization. This study aims to build an android based application that can provide information about tourist attractions in Kuningan Regency. In this application, it will display 3D objects and videos of each tourist attraction. In making this application the technology used is Augmented Reality using the Marker Based Tracking method which is a method in Augmented Reality that requires markers as markers, these markers usually feature black edges and white backgrounds. The Speeded-Up Robust Features (SURF) algorithm is used to detect local features of an image and to design a system using the Unified Modeling Language (UML). The final result of this research is an Augmented Reality application that displays information in the form of 3D objects and interactive tourist attraction videos. It is hoped that this application can help DISPORAPAR in socialization activities and make it easier for people to get information about tourist attractions in Kuningan Regency. Keywords : The Kuningan District Sports and Tourism Department (DISPORAPAR), Travel Attractions, Augmented Reality, Based Tracking Marker, Speeded-Up Robust Features (SURF).